EXAMINING THE REASONS OF BOXING TRAINERS AND REFEREES WHO PLACE SPORTS BETTING - KARADAĞ , Mustafa (SSD Journal, 2022)
Purpose: Sports Betting Games; It includes the reasons that are effective in people's desire to earn a lot of money, sometimes their leisure hobby, and sometimes their big dreams. So that; These reasons also become habits in people over time and affect the frequency and habits of playing sports bets. Therefore, the purpose of this research is to examine the reasons for the boxing referees and trainers, who are involved in sports, to play sports bets.Material Method: The universe of the research; The referees and trainers who participated in the Turkish Individual Boxing Championship held in Elazig on September 3-9, affiliated with the Turkish Boxing Federation. The sample of the research is; 62 volunteers from these referees and coaches, 50 male and 12 female, who play sports bets. Data obtained at the end of the research SPSS. Data obtained at the end of the research SPSS. It was defined in 22 package programs and the statistical significance level was accepted as p<0.05. In this research, the 7-question sociodemographic variable created by Yüce (2020) and the Sports Betting Addiction Index (SBBI), which consists of 7 dimensions and 37 items related to betting, were used, and the frequency and percentage values and tables were explained. Results: While the rate of those who bet every day is 43.5%, it is seen that 82.3% of them are from the betting dealers. It has been seen that the amount allocated for betting is 40.3%, 50 TL and below. When the findings, which indicate the degree of risk assessment status of the participants, are examined, it is seen that the motivation levels for playing sports bets are generally indicated by the lower levels of "Less" and "A little". Conclusion: It can be said that sports betting games are not at the addiction level of boxing referees and trainers, the amounts they allocate to bets are low and they do not have any expectations from betting.